1997
DOI: 10.3758/bf03211910
|View full text |Cite
|
Sign up to set email alerts
|

Hemispheric asymmetries for the temporal resolution of brief auditory stimuli

Abstract: This study investigates a left-hemisphere (LH) advantage for the discrimination of fine temporal events within the auditory modality in 24 normal adults. Brief noise bursts were delivered monaurally to the left or right ears, half of which contained a gap lasting between 2 and 8 msec. Subjects were required to indicate whether or not the noise burst contained a gap. Research within this area has yielded conflicting results. It is possible that variations in gap position or the properties of the noise burst may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
36
5
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 27 publications
(48 reference statements)
7
36
5
1
Order By: Relevance
“…Why did the allocation of auditory attention affect microsaccade direction only with left cues, and why was the effect in this direction? Brown and Nicholls (1997;also Nicholls et al, 1999) reported a lefthemisphere advantage for processing brief auditory stimuli (like our cue), that is, according to Kinsbourne's (1970) In summary, we report a new effect of auditory attention on oculomotor behavior in the absence of any visual display changes. Microsaccade rate is influenced by visual and auditory stimuli alike, whereas effects are different for microsaccade direction.…”
Section: Discussionsupporting
confidence: 61%
“…Why did the allocation of auditory attention affect microsaccade direction only with left cues, and why was the effect in this direction? Brown and Nicholls (1997;also Nicholls et al, 1999) reported a lefthemisphere advantage for processing brief auditory stimuli (like our cue), that is, according to Kinsbourne's (1970) In summary, we report a new effect of auditory attention on oculomotor behavior in the absence of any visual display changes. Microsaccade rate is influenced by visual and auditory stimuli alike, whereas effects are different for microsaccade direction.…”
Section: Discussionsupporting
confidence: 61%
“…34,35 Our results, however, agree with those of Efron et al, 36 Baker et al, 37 and Musiek et al, 38 in which no perceptual asymmetry was found between ears in gap detection procedures. Baran and Musiek 46 have stated that monochotic tests are useful for detecting alteration in auditory pathways but not for locating these changes, as ipsi-and contralateral pathways participate in this process, which results in similar right and left ear performance.…”
Section: Resultscontrasting
confidence: 48%
“…The failure to find the expected asymmetry in the effects of gaps on the blink reflex, with inhibition evoked by briefer gaps to the right than to the left ear, is in contrast to the general finding of finer temporal resolution of stimuli directed to the right than to the left sensory fields of righthanders and the specific finding of better psychophysical detection of gaps in noise to the right than to the left ear of right-handers (Brown & Nicholls, 1997). This failure of reflex methodology to detect an asymmetry that is detected by psychophysical methods is not a result of its insensitivityto temporal variation; Experiment 3C showed a systematic decline in relative reflex amplitude with millisecond increments in gap duration, and there was no evidence of an asymmetry with 4-and 6-msec gaps, conditions in which Brown and Nicholls found a right-ear advantage.…”
Section: Discussioncontrasting
confidence: 45%